The Synchronic and Diachronic Relation of the Pskov Dialect to its Neighboring Languages (regarding Reporting and Research) - Костючук, Лариса Яковлевна Яковлевна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The collection and research of the Pskov folk speech have resulted in an understanding of the role of synchronic and diachronic relations of the Pskov dialect to its neighboring languages in the borderzone. Certain unique peculiarities of the Pskov dialect distinguish it from the East Slavic languages and all Russian dialects. The multi-faceted lexicographic work on the Pskov Regional Dictionary with Historical Data compels us to search for the explanation of specific dialectic aspects of certain words (кеп, всегли, мочигло, подпояхаться, приведи булку, etc.) and to find investigational solutions that change established academic judgments. Archaeological data are relevant for the study of the Pskovian ancestors’ contacts with the native speakers of other linguistic systems (Baltic and Finno-Ugrian in the first place). The 20th century has demonstrated that records of the folk speech throughout all stages of preservation must be accurate, as the consideration of even rare facts may lay the foundation of an important discovery and new theoretical conclusions. Lexicography reflects and preserves knowledge of the Pskov dialect’s past and present contacts with the Baltic and Finno-Ugrian people. Results of the academic research of unique aspects of the Pskov dialect (the lack of the second palatalization in bases кеп-, кев-, кед-; unusual consonant blends [гл], [кл]; the peculiar appearance of the sound [х]: мяхо, спрахывать; an exchange of sibilants and fricatives: суба “шуба”, etc.) have justified the special position of the dialect among East Slavic languages and all Russian dialects.
Keywords: Pskov dialect, Pskov Regional Dictionary with Historical Data, multilevel dialect peculiarities, lack of the second palatalisation, lack of consonant blends reduction, borderzone with Baltic and Finno-Ugrian languages, archaeology